The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c8ra08780f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of MgAl-DBS LDH/PLA composite by sonication-assisted masterbatch (SAM) melt mixing method

Abstract: This research work is based on the comparison of the mixing phenomena of magnesium–aluminum (MgAl) layered double hydroxides (LDHs) intercalated by dodecylbenzene sulfonate (MgAl-DBS) in poly(lactic acid) (PLA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 61 publications
2
26
1
Order By: Relevance
“…Calorimetric analysis revealed that the Extrudr BDP Flax sample exhibited three representative transformations, the first at 62.7 • C (inflection point), which can be associated with the glass transition of amorphous material components (probably PLA or copolyester), [24,25], followed by the ascending slope, which suggests an enthalpy relaxation, [26,27]. The exothermic peak at 124.5 • C (curve II) that takes place with a heat release within the 109.9-136.3 • C temperature range, could correspond to the hot crystallization of the material, the process taking place with minimal energy consumption [24,25]. The Curve III endothermic peak at 154.1 • C corresponded to the melting point of the material.…”
Section: Of 21mentioning
confidence: 99%
“…Calorimetric analysis revealed that the Extrudr BDP Flax sample exhibited three representative transformations, the first at 62.7 • C (inflection point), which can be associated with the glass transition of amorphous material components (probably PLA or copolyester), [24,25], followed by the ascending slope, which suggests an enthalpy relaxation, [26,27]. The exothermic peak at 124.5 • C (curve II) that takes place with a heat release within the 109.9-136.3 • C temperature range, could correspond to the hot crystallization of the material, the process taking place with minimal energy consumption [24,25]. The Curve III endothermic peak at 154.1 • C corresponded to the melting point of the material.…”
Section: Of 21mentioning
confidence: 99%
“…9 The possibility to intercalate organic compounds into the layers of the LDHs also make them useful for multifunctional applications, such as usage in dye sensitized solar cells, enhancement of ame retardant properties, and resistance to thermal degradation. [10][11][12][13][14][15][16] Most recently, the development of novel layered materials attracts great interest in various elds. [17][18][19][20][21] There exist many techniques to prepare LDHs, the most common being co-precipitation, urea hydrolysis, ion exchange and hydrothermal synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, adsorption affinity of the surface area of the adsorbent is independent of the surface area and dependent on the favorable attractive interactions present at the pH value range below 7. When the pH is higher than 7, the electrostatic repulsion forces of the adsorbate-adsorbent are weakened, hence, the reduced adsorption efficiency or removal percentage of contaminants [41,49,131]. The adsorption of contaminants from water mostly depends on hydrophobic interactions between adsorbate and adsorbent, which make great contributions to the affinity of the organic anion to LDH.…”
Section: Adsorption Of Polymer/nanoclay and Ldh Systemsmentioning
confidence: 99%